Demotivation Factors in Using English as A Daily Communication in EFL School: Faktor Demotivasi Penggunaan Bahasa Inggris sebagai Komunikasi Sehari-hari di Sekolah EFL - Heri Pranatan (LPPM Institut Studi Islam Sunan Doe, 2022)
This study was aimed at describing the causes of students’ demotivation in using English for daily communication as well as to find its solutions. The present researcher used descriptive qualitative method. It was conducted in SMP Islam Abul Barakat for the eighth graders of junior high school. There were 15 students to be participants in this study. The data were collected by observing, interviewing and giving questionnaire the participants about the usage of English in their Islamic boarding school. The participants’ answer and the video of their daily communication were analyzed to find out the causes of students’ demotivation in using English as daily communication and also its solution. The result analysis showed the causes of students’ demotivation is their lack ability in using English specially in mastering vocabulary and its pronunciation. Other factors were learning contents and materials, teachers and failure experience. In addition, they prefer to use Arabic because Arabic has been rooting as daily communication in that Islamic boarding school. While the solution for that problem is the teachers should put a big attention to the students’ English ability especially in mastering and pronouncing vocabulary. Also, the teachers are suggested to pay more attention to the choice of teaching methods and their behavior that can increase students’ motivation and interest in second language learning. In addition, the teachers should make a regulation explicitly to divide a period of time for the student to speak English and also Arabic.